A formação continuada das professoras da rede parceira da educação infantil no município de São Paulo - Santana, Angelina V. Ap. Colombo (2019)
This study aims at analyzing and comparing the continued education of teachers of the Children’s Education Centers (old day cares) from the direct and partner public schools (indirect and affiliated) from Sao Paulo City Hall, based on the fact that there is an inequality scenario concerning the continued education of teachers from the partner schools (indirect and affiliated) provided by the County Secretary of Education. The study main objective is to analyze such education among the public schools through informative material from the Regional Board of Campo Limpo , which contributed to this survey. The methodology used is qualitative analyzing official documents such as Decrees, Administrative Rules, and Normative Guidance, Laws and Resolutions and bibliographic material. This study is founded in the following authors: Novóa(2009), Carlos Marcelo Garcia(1995), Maúes (2006), Saviani(2009), Maria Malta (1999).